2023
DOI: 10.3390/jcm12031148
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Quality of Life Benefits for End-Stage Workers’ Compensation Chronic Pain Claimants following H-Wave® Device Stimulation: A Retrospective Observational Study with Mean 2-Year Follow-Up

Abstract: Previously promising short-term H-Wave® device stimulation (HWDS) outcomes prompted this retrospective cohort study of the longer-term effects on legacy workers’ compensation chronic pain claimants. A detailed chart-review of 157 consecutive claimants undergoing a 30-day HWDS trial (single pain management practice) from February 2018 to November 2019 compiled data on pain, restoration of function, quality of life (QoL), and polypharmacy reduction into a summary spreadsheet for an independent statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…A cohort survey study of first responders using HWDS made available at the job site demonstrated multiple work-related performance improvements [ 48 ]. A large observational cohort study of end-stage workers’ compensation chronic (mean 8 years) pain patients found that HWDS treatment led to significant QoL gains, in terms of improved function, reported pain, and decreased medication use [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…A cohort survey study of first responders using HWDS made available at the job site demonstrated multiple work-related performance improvements [ 48 ]. A large observational cohort study of end-stage workers’ compensation chronic (mean 8 years) pain patients found that HWDS treatment led to significant QoL gains, in terms of improved function, reported pain, and decreased medication use [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ], this small study provides additional anti-pain positive clinical metrics. In future studies, we can compare larger case groups to gain additional insights into the value of this approach to protocol building to address the complexity of severe chronic pain, whether lengthy [ 52 ] relatively short in duration.…”
Section: Discussionmentioning
confidence: 99%
“…Norwood et al reported patient-recorded outcome measures (PROMs) for 2,711 non-specific chronic low back pain, sprain, strain HWDS patients, resulting in substantial pain improvement (3.12 on a 0–10 visual analogue scale), with profound positive effects on function and ADL, in addition to benefits like decreased medication use, better sleep, and improved work performance ( 14 ). Trinh et al in a large retrospective cohort study involving end-stage worker's compensation patients, reported no adverse effects associated with HWDS, with significant reduction in pain, opioids/polypharmacy use, and anxiety/depression, while improving overall QoL ( 2 ). Williamson et al in a retrospective cohort study involving first responder firefighters, reported easy device use and no untoward side-effects with HWDS, with statistically significant reduction in reported pain, improvements in ROM and job performance, and increased time spent with family, leading to overall positive health benefits and experience ( 1 ).…”
Section: Mechanism Of Action and Effectiveness On Pain And Functionmentioning
confidence: 99%
“…Chronic musculoskeletal pain, stemming from soft tissue inflammation and injury, has been estimated to occur in up to half of adults worldwide, accounting for hundreds of billions of dollars in healthcare costs ( 1 , 2 ). Functional deficits including decreased range of motion (ROM) and interference with activities of daily living (ADL) are frequently associated with persistent pain ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation